Aldehyde dehydrogenase 2 and NOD-like receptor thermal protein domain associated protein 3 inflammasome in atherosclerotic cardiovascular diseases: A systematic review of the current evidence - Shi, Xue-yun; Yue, Xiao-lin; Xu, You-shun; Jiang, Mei; Li, Rui-jian (Frontiers in Cardiovascular Medicine, 2023)
Inflammation and dyslipidemia underlie the pathological basis of atherosclerosis (AS). Clinical studies have confirmed that there is still residual risk of atherosclerotic cardiovascular diseases (ASCVD) even after intense reduction of LDL. Some of this residual risk can be explained by inflammation as anti-inflammatory therapy is effective in improving outcomes in subjects treated with LDL-lowering agents. NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome activation is closely related to early-stage inflammation in AS. Aldehyde dehydrogenase 2 (ALDH2) is an important enzyme of toxic aldehyde metabolism located in mitochondria and works in the metabolism of toxic aldehydes such as 4-HNE and MDA. Despite studies confirming that ALDH2 can negatively regulate NLRP3 inflammasome and delay the development of atherosclerosis, the mechanisms involved are still poorly understood. Reactive Oxygen Species (ROS) is a common downstream pathway activated for NLRP3 inflammasome. ALDH2 can reduce the multiple sources of ROS, such as oxidative stress, inflammation, and mitochondrial damage, thereby reducing the activation of NLRP3 inflammasome. Further, according to the downstream of ALDH2 and the upstream of NLRP3, the molecules and related mechanisms of ALDH2 on NLRP3 inflammasome are comprehensively expounded as possible. The potential mechanism may provide potential inroads for treating ASCVD.